2021
DOI: 10.1016/j.exphem.2020.09.194
|View full text |Cite
|
Sign up to set email alerts
|

Reading the B-cell receptor immunome in chronic lymphocytic leukemia: revelations and applications

Abstract: B-Cell receptor (BCR) sequencing has been the force driving many recent advances in chronic lymphocytic leukemia (CLL) research. Here, we discuss the general principles, revelations, and applications of reading the BCR immunome in the context of CLL. First, IGHV mutational status, obtained by measuring the mutational imprint on the IGHV gene of the CLL clonotype, is the cornerstone of CLL risk stratification. Furthermore, the discovery of "BCR-stereotyped" groups of unrelated patients that share not only a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Although CLL is generally of monoclonal origin, multiple productive IGH rearrangements have been observed in around 2% of CLL cases (16). These can arise from a single CLL clone (biallelic rearrangement) or reflect biclonal CLL disease (41,42). Interestingly, family member 1D appeared to have biclonal CLL consisting of a SmIgk+ and a SmIgl+ CLL clone as determined by flow cytometry (data not shown).…”
Section: Familial Cll Shows Consistent Bcr Ig Characteristicsmentioning
confidence: 86%
“…Although CLL is generally of monoclonal origin, multiple productive IGH rearrangements have been observed in around 2% of CLL cases (16). These can arise from a single CLL clone (biallelic rearrangement) or reflect biclonal CLL disease (41,42). Interestingly, family member 1D appeared to have biclonal CLL consisting of a SmIgk+ and a SmIgl+ CLL clone as determined by flow cytometry (data not shown).…”
Section: Familial Cll Shows Consistent Bcr Ig Characteristicsmentioning
confidence: 86%
“…S8 ). Although true bi- or oligoclonality is an infrequent phenomenon in B-cell lymphoproliferative disorders 37 , 38 , biclonality has been reported mostly in the context of composite lymphomas 39 41 , and also within single lymphoma subtypes 42 , 43 and in immunosuppressed patients 44 , 45 . It is known that, especially in patients with a history of infectious mononucleosis or immune deficiencies, EBV latent antigens can regulate or mimic different survival and proliferative signaling pathways, and thereby promote lymphomagenesis 46 – 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown reliable detection of MRD down to 10 À6 by NGS. 45,46 In ALL, NGS has been cited to be more accurate than current universal methods, including PCR. 47 In another study with 378 samples spanning ALL, MM, and MCL, there was good correlation between PCR and NGS MRD (R ¼ 0.8; P , .001); furthermore, NGS had at least the same degree of sensitivity as PCR without the need for patient-specific primers.…”
Section: Discussionmentioning
confidence: 99%